Using real time PCR to detect shigellosis: ipaH detection in Kaeng-Khoi District, Saraburi Province, Thailand - Samosornsuk, S.; Chaicumpa, W.; Seidlein, L. von; Clemens, J.D.; Sethabutr, O. (Science & Technology Asia, 2015)
-